Mapping narratives of urban resilience in the global south. (January 2019) - Borie, Maud; Pelling, Mark; Ziervogel, Gina; Hyams, Keith
Highlights: We map different narratives of urban resilience in Manila, Nairobi, and Cape Town. These narratives are associated with diverse forms of knowledge and expertise. Science methods can empower the most vulnerable or reinforce existing inequalities. The processes of developing resilience strategies are key to ensure their legitimacy. Recognizing this diversity of narratives can facilitate inclusive resilience policy. Abstract: In the context of global environmental change much hope is placed in the ability of resilience thinking to help address environment-related risks. Numerous initiatives aim at incorporating resilience into urban planning practices. The purpose of this paper is to open up a conversation on urban resilience by unpacking how diverse science methods contribute to the production of different narratives of urban resilience mobilizing different experts and forms of evidence. A number of scholars have cautioned against uncritical approaches to resilience and asked what resilience means and for whom, also pointing out the normative dimension of the concept. Building on this emerging scholarship we use insights from science and technology studies (STS) and critical social sciences to look at the knowledge infrastructures and networks of actors involved in the development of resilience strategies. Drawing on fieldwork in Manila, Nairobi, and Cape Town, we map different narratives of urban resilience identifying the ways in which science serves to legitimate or alienate particular perspectives on what should be done. We discuss the multiple roles that science methods have for resilience planning. Whereas urban resilience is often portrayed as consensual, we show that a range of narratives, with diverse socio-material implications, exist at the city level. In this way we unearth the conflict that lies beneath an apparent consensus for resilience policy and outline future research directions for urban sustainability.